A Distinctive Perceptions of the Disputants in the Negotiation of Labor Dispute Resolution - Abigail, Dan-Mallam Yakubu; Karubi, Peter Nwanes; Parveen, Kaur; Arif, Jawaid; Nazir, Hussain Shah; Khalil, Ur Rehman (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Negotiation is a method by which disputing parties settle their differences. It is a process by which compromise or agreement is reached while avoiding argument or dispute. However, the success of every negotiation depends largely on the disputant’s perceptions of each other on the negotiation table. This study investigated the influence of the perceptions of the representatives of the Academic Staff Union of Universities (ASUU) and the representatives of the Federal Government of Nigeria (FGN) in the negotiation process. In order to achieve the objectives of this study, a qualitative approach was adopted. A total number of 42 participants were interviewed through an in-depth face to face interview, 23 representatives from the side of the FGN and 19 representatives from ASUU. Findings from this study revealed that ASUU and the Nigeria government have not been able to resolve their labor dispute because of the government insincere and dishonest behavior in-terms of the implementation of her agreement reached with ASUU at the negotiation table. This study also found lack of explanation and apology from the side of the Nigeria government to ASUU especially when the government fail to implement the agreement reached by both parties. In contrast, the result of this study indicates that greed and selfishness, lack of compromise as their common perceptions of the representatives of the government about ASUU which often influence the successful outcome of the negotiation for some decades. This study concluded that, disputants cannot achieve a fruitful resolution outcome without a sincere and honest communication between the two parties at the negotiation table. In addition, negotiators cannot also reach a satisfactory win-win settlement point without cooperation and compromise between the two parties.